Characterization and burden of Campania children health migration across Italian regions during years 2006-2010: chance and/or necessity? - Vajro Pietro; Paolella Giulia; Celentano Egidio; Longo Giuseppe; Saccheri Tullia; Pinto Claudio; Masullo Giuseppe; Scafarto Virginia; Bianchi Attilio (BMC, 2012)
Abstract Background To evaluate medical, economical and sociological variables underlying avoidable pediatric migration from Campania region. Methods Analysis of years 2006-2010 hospital discharge records, extracted from the archive of Regional Health Agency (ArSan), classified by Major Diagnostic Categories, Aggregate Clinical Codes, Discipline of dismissal, Local Health Authorities of residence, and age group 0-14 years (excluding those of healthy newborns). Sociological variables were evaluated by questionnaires. Results A total of 68,316 hospital discharge records were released by extra-regional structures. Major diagnostic categories and Discipline of dismissal indicated that the most implicated diseases (nervous system and mental disorders, hematology-oncology, and bone diseases) were not always of very high complexity. The total cost paid by the Campania Region was 124.700.000 Euros. The need for more specialized hospital pediatric units and/or with more pediatric subspecialties in the native region was pointed out by most of the self-administered questionnaires. Conclusions Pediatric migration is an important phenomenon with evident implications. The identification of the most concerned sub-specialties here reported can give useful information aiming to assist in the improvement of the existing pediatric resources in Campania region in the wider context of the national global child health advancement.